Evidence for a Specific Diabetic Cardiomyopathy: An Observational Retrospective Echocardiographic Study in 656 Asymptomatic Type 2 Diabetic Patients - Isabelle Pham; Emmanuel Cosson; Minh Tuan Nguyen; Isabela Banu; Isabelle Genevois; Patricia Poignard; Paul Valensi (International Journal of Endocrinology)
Aim. Our aim was to assess the prevalence of subclinical diabetic cardiomyopathy, occurring among diabetic patients without hypertension or coronary artery disease (CAD). Methods. 656 asymptomatic patients with type 2 diabetes for 14 ± 8 years (359 men, 59.7 ± 8.7 years old, HbA1c 8.7 ± 2.1%) and at least one cardiovascular risk factor had a cardiac echography at rest, a stress cardiac scintigraphy to screen for silent myocardial ischemia (SMI), and, in case of SMI, a coronary angiography to screen for silent CAD. Results. SMI was diagnosed in 206 patients, and 71 of them had CAD. In the 157 patients without hypertension or CAD, left ventricular hypertrophy (LVH: 24.1%) was the most frequent abnormality, followed by left ventricular dilation (8.6%), hypokinesia (5.3%), and systolic dysfunction (3.8%). SMI was independently associated with hypokinesia (odds ratio 14.7 [2.7–81.7], p<0.01) and systolic dysfunction (OR 114.6 [1.7–7907], p<0.01), while HbA1c (OR 1.9 [1.1–3.2], p<0.05) and body mass index (OR 1.6 [1.1–2.4], p<0.05) were associated with systolic dysfunction. LVH was more prevalent among hypertensive patients and hypokinesia in the patients with CAD. Conclusion. In asymptomatic type 2 diabetic patients, diabetic cardiomyopathy is highly prevalent and is predominantly characterized by LVH. SMI, obesity, and poor glycemic control contribute to structural and functional LV abnormalities.